BHIKHU PAREKH CRITICS TOWARD MODERN PLURALISM - Fejrian Yazdajird Iwanebel (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2016)
Pluralism is judged by some thinkers as a response to their dissatisfaction with monism. The factual realities have made a self-evident that society's culture is plural. In this paper the author tries to describe three prominent figures who discuss about pluralism and the weaknesses of their thoughts. The author stands on the work of Bhikhu Parekh entitled